2020
DOI: 10.1038/s41598-020-62756-8
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral proinflammatory Th1/Th17 immune cell shift is linked to disease severity in amyotrophic lateral sclerosis

Abstract: Neuroinflammation is involved in the pathogenesis of amyotrophic lateral sclerosis (ALS), but only limited data are available on systematic peripheral and central immune cell profiles in ALS. We studied detailed immune profiles of 73 ALS patients and 48 healthy controls (controls) in peripheral blood by fluorescence-activated cell sorting as well as cytokine expression profiles in serum. In a subgroup of 16 ALS patients and 10 controls we additionally studied cerebrospinal fluid (CSF) samples. In peripheral bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
119
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(124 citation statements)
references
References 66 publications
(84 reference statements)
4
119
1
Order By: Relevance
“…low numbers are predictive for rapid disease progression and short survival ( Fig. 4 ) ( Henkel et al , 2013 ; Sheean et al , 2018 ), whereas there is moderate negative correlation between Th1 and Th17 T cells, ALSFRS-R and forced vital capacity ( Jin et al , 2020 ). Another study observed a positive correlation between high baseline neutrophil-to-lymphocyte ratio and shorter survival, proposing that it can reflect the degree of neuroinflammation in ALS patients ( Choi et al , 2020 ).…”
Section: Cns Macrophage and Peripheral Immune Cell Contribution To Almentioning
confidence: 99%
See 1 more Smart Citation
“…low numbers are predictive for rapid disease progression and short survival ( Fig. 4 ) ( Henkel et al , 2013 ; Sheean et al , 2018 ), whereas there is moderate negative correlation between Th1 and Th17 T cells, ALSFRS-R and forced vital capacity ( Jin et al , 2020 ). Another study observed a positive correlation between high baseline neutrophil-to-lymphocyte ratio and shorter survival, proposing that it can reflect the degree of neuroinflammation in ALS patients ( Choi et al , 2020 ).…”
Section: Cns Macrophage and Peripheral Immune Cell Contribution To Almentioning
confidence: 99%
“…4A ). Data to support this neuroprotective to neurotoxic shift came largely from studies in mutant hSOD1 ALS models, in which the initial presymptomatic and early symptomatic phases are dominated by anti-inflammatory immune responses (anti-inflammatory microglia, Treg and Th2 CD4 T cells), whereas late symptomatic and terminal stages are dominated by proinflammatory immune responses (proinflammatory microglia and astrocytes, inflammatory monocytes, cytotoxic CD8 T cells, Th1 and Th17 CD4 T cells, NK cells and neutrophils) ( Henkel et al , 2013 ; Zhao et al , 2013 ; Murdock et al , 2017 ; Sheean et al , 2018 ; Choi et al , 2020 ; Garofalo et al , 2020 ; Jin et al , 2020 ). As previously discussed, once that a hyperinflammatory state of microglia or astrocytes is established, these glial cells directly become toxic and can kill motoneurons ( Roberts et al , 2013 ; Re et al , 2014 ; Zhao et al , 2015 ).…”
Section: How Does Immunity Turn From Friend To Foe During Als?mentioning
confidence: 99%
“…Infiltrated T lymphocytes were found in the post-mortem spinal cord of ALS patients ( Engelhardt et al, 1993 ). Studies evaluating immune cell profiles in the peripheral blood of healthy controls and ALS patients showed no differences in levels of total lymphocytes or CD3 + T lymphocytes, however, highlighted differences within specific T cell subsets ( Saresella et al, 2013 ; Shin et al, 2013 ; Chen et al, 2014 ; Jin et al, 2020 ). ALS patients have significantly lower proportions of CD4 + T cells with unchanged or elevated CD8 + T cell proportions ( Chen et al, 2014 ; Jin et al, 2020 ).…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Studies evaluating immune cell profiles in the peripheral blood of healthy controls and ALS patients showed no differences in levels of total lymphocytes or CD3 + T lymphocytes, however, highlighted differences within specific T cell subsets ( Saresella et al, 2013 ; Shin et al, 2013 ; Chen et al, 2014 ; Jin et al, 2020 ). ALS patients have significantly lower proportions of CD4 + T cells with unchanged or elevated CD8 + T cell proportions ( Chen et al, 2014 ; Jin et al, 2020 ). Despite this decreased CD4:CD8 T cell ratio, only a higher CD4 + T cell percentage in ALS patients correlates with disease severity and progression ( Shi et al, 2007 ; Chen et al, 2014 ).…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
See 1 more Smart Citation